2015
DOI: 10.2139/ssrn.2577285
|View full text |Cite
|
Sign up to set email alerts
|

What Do Subjective Assessments of Financial Well-Being Reflect?

Abstract: is to produce first-class research and forge a strong link between the academic community and decision-makers in the public and private sectors around an issue of critical importance to the nation's future. To achieve this mission, the Center sponsors a wide variety of research projects, transmits new findings to a broad audience, trains new scholars, and broadens access to valuable data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Robb et al () explained this result, in part, as individuals basing decisions “solely on biased estimates and inaccurate self‐perceptions” (p. 432). Another possible explanation is that the objective financial knowledge questions, which all relate to financial planning for the future (what Sass et al () has referred to as “distant financial deficits” (p. 21)), may be an indirect measure of present vs. future time preference. The subjective financial knowledge question is not anchored to a time period.…”
Section: Limitations Discussion and Conclusionmentioning
confidence: 99%
“…Robb et al () explained this result, in part, as individuals basing decisions “solely on biased estimates and inaccurate self‐perceptions” (p. 432). Another possible explanation is that the objective financial knowledge questions, which all relate to financial planning for the future (what Sass et al () has referred to as “distant financial deficits” (p. 21)), may be an indirect measure of present vs. future time preference. The subjective financial knowledge question is not anchored to a time period.…”
Section: Limitations Discussion and Conclusionmentioning
confidence: 99%
“…Further interesting findings arise when we explore the fuzzy measures at the country level in relation to important socio-economic and demographic characteristics, as suggested by different contributions of the FW literature (see, e.g. Van Praag et al, 2003: Arber et al, 2014Sass et al, 2015;CFPB, 2015;Br€ uggen et al, 2017). In particular, we consider the following: (1) household income (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Shim et al (2010) employed both objective (amount of debt) and subjective measure (financial satisfaction and coping with financial strain) in operationalising the financial well-being. The school of thought for the combination of objective and subjective measure suggested that individual's subjective well-being is related to individual's financial condition whereby the rich people are happier and more satisfied with their life compare to the poor ones (Sass, Belbase, Cooperrider, & Ramos-Mercado, 2015).…”
Section: Defining Financial Well-beingmentioning
confidence: 99%